Mutational Analyses of the Enzymes Involved in the Metabolism of Hydrogen by the Hyperthermophilic Archaeon Pyrococcus furiosus - Schut, Gerrit J.; Nixon, William J.; Lipscomb, Gina L.; Scott, Robert A.; Adams, Michael (Frontiers in Microbiology, 2012)
Pyrococcus furiosus grows optimally near 100°C by fermenting carbohydrates to produce hydrogen (H2) or, if elemental sulfur (S0) is present, hydrogen sulfide instead. It contains two cytoplasmic hydrogenases, SHI and SHII, that use NADP(H) as an electron carrier and a membrane-bound hydrogenase (MBH) that utilizes the redox protein ferredoxin. We previously constructed deletion strains lacking SHI and/or SHII and showed that they exhibited no obvious phenotype. This study has now been extended to include biochemical analyses and growth studies using the ΔSHI and ΔSHII deletion strains together with strains lacking a functional MBH (ΔmbhL). Hydrogenase activity in cytoplasmic extracts of various strains demonstrate that SHI is responsible for most of the cytoplasmic hydrogenase activity. The ΔmbhL strain showed no growth in the absence of S0, confirming the hypothesis that, in the absence of S0, MBH is the only enzyme that can dispose of reductant (in the form of H2) generated during sugar oxidation. Under conditions of limiting sulfur, a small but significant amount of H2 was produced by the ΔmbhL strain, showing that SHI can produce H2 from NADPH in vivo, although this does not enable growth of ΔmbhL in the absence of S0. We propose that the physiological function of SHI is to recycle H2 and provide a link between external H2 and the intracellular pool of NADPH needed for biosynthesis. This likely has a distinct energetic advantage in the environment, but it is clearly not required for growth of the organism under the usual laboratory conditions. The function of SHII, however, remains unknown.